PENGARUH CAPITAL ADEQUACY RATIO DAN NON PERFORMING FINANCING TERHADAP PROFITABILITAS BANK UMUM SYARIAH DI INDONESIA - Rana Fathinah Ananda (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2020)
This study is aimed to analyze and determined whether the Capital Adequacy Ratio and Non Performing Financing effect simultaneously and partially on the Profitability of Islamic Banks in Indonesia. The population and sample of this research are the Indonesian Sharia Banks which are registered in Bank Indonesia for the year from 2010 until 2019, as many as 13 Banks with saturated sampling techniques in order to obtain 13 Banks. The data analysis in this research is quantitative analysis with the data analysis method used in this study using multiple linear regression analysis and panel data regression selection by doing the Chow test, Hausmant test and Lagrange Multiplier test using Eviews software. The results of this research shows that simultaneously the Capital Adequacy Ratio and Non-Performing Financing, both have a significant effect on Profitability. Partially, the results of the hypothesis test show that the Capital Adequacy Ratio variable has a positive but insignificant effect on ROA in IslamicBanks in Indonesia, while Non Performing Financing has a significant negative effect on the Probability of IslamicBanks in Indonesia.